(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The history of Buddhism traverses very nearly 2,500 years from its root in India with Siddhattha Gotama (Pali, Skt Siddhārtha Gautama), through its spread to most pieces of Asia and, in the twentieth and twenty-first hundreds of years, toward the West. The English expression ’Buddhism’ effectively demonstrates that the religion is portrayed by a commitment to ’the Buddha’, ’Buddhas’ or ’buddha-hood’. ’Buddha’ is anything but an appropriate name, yet a clear title signifying ’Enlightened One’ or ’Enlightened One’. This infers a great many people are seen, in a spiritual sense, as being sleeping – uninformed of how things truly are. Buddhist texts were at first passed on orally by priests, yet were later recorded and formed as original copies in different Indo-Aryan languages which were then converted into other neighborhood languages as Buddhism spread. They can be arranged in various ways. In this examination paper we learned about the Modern Buddhist Literature and its distinctive Characteristics.